Physiotherapy approach in children with Duchenne Muscular dystrophy: Therapy Taping Method - Hardas K Chavda; Madhuben Hardas Chavd (Pediatric Review: International Journal of Pediatric Research, 2021)
Introduction: The Therapy Taping Method (TTM) uses the Therapy Tex® bandage, recommending the use of the bandage for as much time as possible during 24 hours, which can influence motor behavior through neurophysiological effects, providing external support over the body or to an entire segment. Thus, the purpose of this study was to investigate the influence of MTT in the execution of motor functions in children with Duchenne Muscular Dystrophy (DMD). Materials & Methods:Patients with confirmed clinical diagnosis of DMD were included in the study. The confirmation was done by genetic testing and muscle biopsy. Patients were selected from the opd of the paediatric department of the medical college. A trained expert assesses the degree of motor function in the children with the help o MFM-20-P scale. Results:The initial evaluation showed increased in the D1, D2 and D3 value in both the cases at the end of one month. The evaluation after 6 months showed the value increased in D1, D2 and D3 value and also increase in total score as compared to initial value and evaluation at end of one month Discussion & Conclusion: we can encourage the possibility that the MTT in DMD enables an extension of the proper muscle condition, delaying the loss of ambulation evident at around 8-10 years of age, since in both cases there was an increase score in the dimension 1 (D1) and in total score. The overall posture balance was improved in both the children. Also there was reduction in pain after the application of bandage.